THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE (Konferensiyalar | Conferences, 2024)
Professional language training evolves to meet contemporary demands, striving to cultivate competitive individuals equipped to thrive in a globalized landscape. Higher education institutions are increasingly adopting internationally recognized standards, prioritizing the development of English language proficiency and professional capabilities. However, there's a notable gap in understanding the formation of Foreign Language Communicative Competence (FLCC) among aspiring professionals in non-native English-speaking nations. Drawing from our teaching experience in foreign language universities, it's evident that many students lack the requisite English proficiency for effective professional communication. In response, we have formulated a theoretical and methodological framework for analyzing FLCC. Our objective was to devise a pedagogical model incorporating sequential stages and technology to foster students’ motivation, readiness in FLCC, communicative skills, and self-directed learning abilities. This approach entails a systematic progression in competency development, incorporating activities designed to refine perception and provide constructive feedback. The efficacy of our model was confirmed through experimental validation.